Updated range distribution of the non-native Asian green mussel Perna viridis (Linnaeus, 1758) at Guanabara Bay, Rio de Janeiro, Brazil - Luciana V. R. de Messano; José E. A. Gonçalves; Alexandre D. Kassuga; Alexandre R. da Silva; Bruno P. Masi; Héctor F. Messano; Denny Fardin; Ricardo Coutinho (PeerJ, 2024)
Guanabara Bay, located at Rio de Janeiro, Brazil, is a highly urbanized and polluted estuary that houses different port areas, shipyards, and marinas of intense maritime traffic. This infrastructure is widely associated with the introduction and spread of non-native sessile species. A rapid assessment of non-native benthic sessile species conducted in the bay in late 2022 across 19 sites identified a total of 83 taxa, both native and non-native, classified into the following main groups: one Cyanophyta, 13 Macroalgae, 14 Porifera, 11 Cnidaria, six Bryozoa, five Annelida, 10 Mollusca, six Crustacea, 10 Echinodermata, and seven Ascidiacea. Our findings revealed the proliferation of the Asian green mussel (Perna viridis Linnaeus, 1758), a species noted for its exceptional ability to achieve extremely high biomass levels globally. In Brazil, the bivalve was first reported less than 6 years ago in 2018 at Guanabara Bay, on a mariculture farm at Arraial do Cabo (200 km away) in 2023 and more recently in the south (Paranaguá Bay), besides two coastal islands outside Guanabara Bay on natural rocky shores. The present survey recorded P. viridis at 17 sites, including natural substrata, co-occurring with native species. No Tubastraea spp. were observed in Guanabara Bay. Controlling and mitigating the consequences of bioinvasion events can be challenging, but biosafety protocols should be adopted in the near feature to minimize the risks and impacts caused by species dispersal.